Growing seasons and fractional fertilization for arugula - Filho, Arthur Bernardes Cecílio [UNESP]; Maia, Marcela Machado [UNESP]; Mendoza-Cortez, Juan Waldir [UNESP]; Rodrigues, Marilsa Aparecida [UNESP]; Nowaki, Rodrigo Hiyoshi Dalmazzo [UNESP] (My University, 2014)
Aiming to evaluate the splitting of nitrogen in growing seasons of rocket, experiments were carried out during periods from 12-11 to 18-12-2007, from 10-1 to 4-4 to 02/20/2008 and 12/05/2008 at Jaboticabal, São Paulo, Brazil. In each experiment, in randomized blocks, were evaluated ten installments (P) of 160 kg ha-1 N, as urea, constituting ten treatments: P1 = 100% at sowing (S), P2 = 50% in S and 16.7% at 7, 14 and 21 days after seeding (DAS), P3 = 50% in S and 25% at 7 and 14 DAS; P4 = 50% in S and 25% for 7 and 21 DAS , P5 = 50% in S and 25% at 14 and 21 DAS; P6 = 33.3% at 7, 14 and 21 DAS; P7 = 50% at 7 and 14 DAS; P8 = 50% for 7 and 21 DAS; P9 = 50% at 14 and 21 DAS; P10 = 25% in S and 25% at 7, 14 and 21 DAS. The spacing between rows and plants was 0.25 and 0.05 m, respectively. We evaluated the height, fresh and dry weight of shoots, leaf area, yield and nitrogen content in the dry matter of the shoot. There was no significant interaction among factors cropping seasons and evaluated traits in installments. All features were influenced by growing seasons, with the highest values obtained in cultures from November to February. The height, fresh and dry weight of shoots and leaf area were affected by split nitrogen fertilization and, in general, lower values of these characteristics were observed when the N application was made only in two installments in coverage. Moreover, the fragmentation of N did not affect foliar N and productivity. Thus, for economic question and similar soil conditions, it is recommended to provide the N in one portion before sowing.
Épocas de cultivo e parcelamento da adubação nitrogenada para rúcula
Keywords: Eruca sativa; Nitrogen; Productivity